The Impact of Russian Educational Policy on the Formation of Georgian Education System - Kurashvili, Lana (European Scientific Journal, ESJ, 2020)
The study examined the impact of Russian educational policy on the development of the education system in Georgia. It determines the factors influencing formation of the Georgian educational system for centuries under Tsarist and Soviet Russia. Despite years of reforms since independence, the issue of reorganizing the Georgian education system and eliminating the legacy of the past has not lost its relevance in the current period. The historical research method was used in order to study, analyze and draw specific conclusions from past events. The article presents the four main periods of Tsarist Russia and the first independent republic of Georgia in 1918-1921, the Soviet Union and modern independent Georgia. The mentioned periods were examined in the four main directions - the importance of education, national language policy, management system and teaching-learning approaches. The research has found that tsarist and Soviet authorities used similarly totalitarian-authoritarian methods to achieve imperial or Soviet party goals. An important difference concerned the importance of education when, unlike the Tsarist one, the Soviet authorities imposed a large mission on education, but in return demanded the existence of an ideologized society. As for the first independent republic of Georgia of 1918-1921 and the educational policy of modern independent Georgia, the educational policies of the mentioned periods coincide in regard of Western values, democratic principles and European approaches to teaching and learning. The educational policy of independent Georgia was characterized by a radical nature aimed at liberating the old school traditions and integrating them into the international educational space.